A fabricação da imagem imperial de Domiciano em moedas e na Aquileida de Estácio (81-96) - Cotrim, Irlan de Sousa (2022)
The fabrication of the imperial image of Domitian (81-96), the last representative of the Flavian dynasty (69-96), was based on the approximation of the princeps with divine, semi-divine and historical figures. In this dissertation, we mobilized a documental corpus that contemplates a set of coins minted in Rome during the fifteen years of Domitian’s government, as well as an epic poem written by Publius Papinius Statius—the Achilleid. In our understanding, the spread of the associations of the emperor’s image with gods, demigods and historical personalities in the coinage and in the poem allowed the cooptation of forces from the senatorial aristocracy, from the army and from the Roman population, which contributed, in this way, to the maintenance of the legitimacy of the princeps. Domitian’s coins constructed, both in inscriptions and images, the figure of the emperor as endowed with virtues such as fortitudo, gloria, concordia, liberalitas and pietas towards the gods and family members, in addition to affiliating Domitian’s military achievements with the Flavian and Augustan precedents. In the Achilleid, Statius compared the emperor to the legendary warrior Achilles and gave the former precedence, in terms of virtues, to the latter's history, besides having constructed the character as an exemplum of martial dexterity and a bearer of pietas, fundamental concepts in the context of the Principate. We use as theoretical framework the concepts of representation and practices, coined by Roger Chartier (1991; 2002), of propaganda, applied to Classical Studies by Paulo Martins (2011) and by Ana Teresa Marques Gonçalves (2013), of theatrocracy, by Georges Balandier (1982), and of symbolic power, by Pierre Bourdieu (2005). In addition, we used the precepts of epideictic rhetoric from ancient treatises such as the writings of Cicero, the Auctor ad Herennium, Quintilian, and Menander the Rhetorician, because we understood that our corpus was inserted in a rhetorical interdiscourse. The method used was content analysis based on the technique of categorical analysis as presented by Laurence Bardin (2011).